Neutral Genetic and Phenotypic Variation within and among Isolated Headwater Populations of Brook Trout. Issue 1 (7th November 2018) - Weathers, T. Casey; Kazyak, David C.; Stauffer, Jay R.; Kulp, Matt A.; Moore, Stephen E.; King, Tim L.; Carlson, John E.
Abstract: Isolated populations are challenging to manage and conserve, as they are particularly vulnerable to genetic drift, allelic fixation, and inbreeding and may express markedly reduced phenotypic variability. We sought to improve our understanding of how spatial isolation, occupancy range, and restricted gene flow influence contemporary phenotypic variation within and among native populations of Brook Trout Salvelinus fontinalis by examining the neutral genetic and phenotypic characteristics of 35 isolated headwater populations from Great Smoky Mountains National Park. Across a suite of 13 neutral microsatellite loci, we observed high levels of allelic fixation and considerable genetic differentiation among populations, subwatersheds, and watersheds that were consistent with patterns of isolation. We found significant positive correlations between allelic diversity and estimates of effective population size. In contrast, we observed considerably less phenotypic structure among streams, subwatersheds, and watersheds. Much of the observed phenotypic variation occurred among individuals within populations. Pairwise Mann–Whitney tests revealed no significant phenotypic differences among the populations of Brook Trout we examined. Similarly, there was no significant relationship between the amount of phenotypic variation within populations and any of the examined measures of genetic diversity or the amount of occupied habitat sampled, which suggests that unmeasured variables may be influencing morphometric and meristic variation within isolated populations. The observed patterns of isolation, genetic drift, and allelic fixation highlight the importance of enhancing population connectivity but also suggest that considerable phenotypic variability may persist within small, fragmented populations. Our results elucidate some challenges associated with managing and conserving isolated populations of Brook Trout and reinforce the importance of conducting genetic studies on fragmented populations to inform management decisions.